Investigate the Relationship between Sensation Seeking and Self-Regulation in Normal and Delinquent Boys in Mashhad, Iran - Masoumeh Rezazadeh; Farideh Nazarzadeh; Hamid Reza Aghamohammadian-Sha’arbaf; Hossein Karshki (Journal of Kerman University of Medical Sciences, 2015)
Background & Aims: The purpose of this study was investigating the relationship of sensation seeking and self-regulation in delinquent and normal adolescent boys. Methods: In this descriptive-correlation study, 80 delinquent adolescent boys who were habitant in Mashhad Training and Improvement Association, Mashhad, Iran, were selected via random simple sampling method; and 80 normal male students of Mashhad high schools were selected using cluster sampling method. Self-regulation questionnaire (SRQ) and Alizadeh sensation seeking index (ASSI) were completed by each of them. ANOVA and t tests were used to analyze the data. Results: There was a significant negative correlation between the self-regulation and the sensation seeking in both groups. In addition, the implementation component in the criminal group, and the measurement component in the normal group showed significant reverse correlation with sensation seeking. Conclusion: Self-regulation could be used as a factor for controlling or changing sensation seeking in delinquent adolescent boys